Galectin-3 in heart transplant rejection and fibrosis - O. P. Shevchenko; A. A. Ulybysheva; O. E. Gichkun; N. P. Mozheiko; E. A. Stakhanova; V. S. Kvan; A. O. Shevchenko (Вестник трансплантологии и искусственных органов)
Aim: to study plasma galectin-3 levels in heart recipients and to determine the potential significance of galectin-3 level in acute transplant rejection and fibrosis.Methods. The study included 107 heart transplant recipients, aged 16 to 70 (48 ± 13) years, of which 90 (84%) were men. Dilated cardiomyopathy was diagnosed in 57 patients prior to heart transplantation, end-stage ischemic heart disease in 50. Galectin-3 concentrations and placental growth factor (PlGF) were measured using enzyme-linked immunosorbent assay (ELISA); vascular endothelial growth factors (VEGF-D and VEGF-A), monocyte chemoattractant protein-1 (MCP-1), platelet-derived growth factors (PDGF-BB), and soluble CD40 ligand (sCD40L) were measured using multiplex technology xMAP. Acute graft rejection and myocardial fibrosis were verified through morphological examination of endomyocardial biopsy specimens.Results. Galectin-3 concentrations in patients with congestive heart failure (15.92 [11.80; 23.65] ng/ ml) were significantly higher than in healthy individuals (11.08 [7.71; 14.47] ng/ml), p = 0.00. No correlation was found between galectin-3 levels and sex, age and pre-transplant diagnosis. A month after transplantation, plasma galectin-3 level was significantly higher than before transplantation; a year later, the levels decreased to pre-transplant levels (18.71 [13.14; 25.41] ng/ml). By the end of the first year after transplantation, the levels were significantly higher both in patients with 1-2 episodes and in the patients after 3 or more episodes of acute rejection, in contrast to recipients who were not diagnosed with rejection. By the end of the first year after heart transplantation in patients with fibrosis, plasma galectin-3 levels were significantly higher than in patients without fibrosis. By the end of the first year after heart transplantation, galectin-3 levels in the recipients were associated with the nature of myocardial fibrosis: in patients with diffuse focal fibrosis (22.52 [20.98; 26.08] ng/ml), plasma concentrations of galectin-3 were significantly higher than in patients without fibrosis (15.36 [11.95; 22.42] ng/ ml, p = 0.01).Conclusion. Plasma levels of galectin-3 in heart recipients by the end of the first year after transplantation is associated with previous crises of acute graft rejection, irrespective of the number of rejection episodes. Elevated plasma levels of galectin-3 in heart recipients in the long term after transplantation is associated with myocardial fibrosis; galectin-3 levels are associated with the morphological characteristic of fibrosis in the transplanted heart (diffuse focal fibrosis).